Design-redesign, implementation, and evaluation of effectiveness of maternal nutrition and responsive parenting program on child development at 2 years of age from rural India: a cluster RCT - Gaidhane, Abhay; Khatib, Mahalaqua Nazli; Telrandhe, Shital; Patil, Manoj; Kogade, Priti; Gaidhane, Shilpa; Choudhari, Sonali G.; Holding, Penny A.; Saxena, Deepak; Syed, Zahiruddin Quazi (Frontiers in Public Health, 2023)
Background: To promote early childhood development (ECD), we require information not only on what needs to be addressed and on what effects can be achieved but also on effective delivery methods that can be adapted to local context. We describe design, implementation, and evaluation of a complex intervention to strengthen nurturing environment for young children.Methods: Study participants were pregnant women and their children from birth to 2 years. We used design and redesign, implementation, and evaluation approaches for the study. We co-created curriculum and delivery plan with stakeholders, based on the theoretical framework, findings from formative research, and our preliminary work. We recruited 656 pregnant women and newborns, 326 (49.69%) from intervention and 330 (50.30%) from the control group. We conducted a cluster randomized controlled trial to evaluate the program's effectiveness. The outcomes of children were assessed at 12 and 24 months.Findings: At recruitment, study participants from both the study arms were similar in sociodemographic characteristics. We conducted 6665 home visits, 25 toy-making workshops, and 65 caregiver-meetings. The initial examination of program data revealed gaps in quality and coverage of interventions. The intervention was redesigned based on feedback from stakeholders in community meetings. At recruitment, participants in both study groups had similar socio-demographics. We conducted 6665 home visits, 25 toy workshops, and 65 caregiver meetings. Initial program data showed intervention quality and coverage gaps, leading to a redesign program based on community & stakeholder feedback. Post-re-designing, session quality improved, with program coverage rising from 32% to 98%. Male participation in home visits increased from 4.3% to 32.65%, and data errors reduced from 270 to 140 per month on average. At 24 months, program showed moderate-mild impact on ECD -cognitive (0.31; 95%CI:0.13-0.48), language (0.2; 95%CI: 0.01-0.39), and socioemotional-development (0.19; 95%CI:0.01-0.37), moderate effect on homeenvironment and mother-child interaction. 96% of women initiated breastfeed within onehour of delivery, and exclusive-breastfeeding rate of 89.80%.